"A Voyage of Discovery": Reimagining the Walking Woman through Nineteenth-Century Diaries. Issue 4 (2022) - Bredar, Trish
Abstract : This article uses a corpus of manuscript diaries to illuminate the practices and meanings of everyday mobility that shaped the lives of nineteenth-century Englishwomen. The female pedestrian has typically been characterized by scholars as a marginal or transgressive figure whose movements are interpreted through comparison to a masculine peripatetic tradition. "A Voyage of Discovery" seeks to broaden our understanding of what it meant to move through the world as a woman in the nineteenth century. Drawing from the narrated experiences of a broad range of little-known diarists, this article outlines a paradigm of "everyday adventure" to describe walking's status as an unremarkable act that nevertheless creates the potential for event and variety. In so doing, it expands on feminist concepts of the everyday, elaborates on the under-theorized relationship between walking and the body, and reassesses the boundaries of socially acceptable mobility.